A case-study of secretarial science students' attitudes towards english language / Kamariah Husin - Husin, Kamariah (Universiti Teknologi MARA, Pahang, 1991)
Although there has been a considerable research under taken elsewhere to analyse the English achievement of the college students, not many studies have been carried out as far as Malaysia is concerned. This study apart from attempting to examine the nature of the students' attitudes towards English also tries to fill in the vacuum created. The subject for this study consisted of 45 Part III and Part IV Secretarial Science students randomly selected from the population. The attitudinal variables incorporated into the analysis are measured through the following components: i) students' perception of English as a subject ii) profitability of learning the language iii) whether it is boring or not iv) studying English because of no choice v) to secure good jobs vi) its relevance to the course vii) the usefulness of the language to be learnt by everyone The results indicated that the role of the attitudinal variables was more dominant for the final year students but not for the semester III group. In the latter case it seems that other factors might have played a part in affecting their achievement in English.